FRI0615 EVALUATION OF COMPLIANCE AND RELATED FACTORS IN COLCHICINE TREATMENT IN FAMILIAL MEDITERRANEAN FEVER PATIENTS. (June 2019) - Tekgoz, Emre; Colak, Seda; Cinar, Fatma İlknur; Yilmaz, Sedat; Çınar, Muhammet
Abstract : Background: Familial Mediterranean Fever (FMF) is an autoinflammatory disease requiring long-term treatment. Increasing the compatibility with colchicine treatment in patients with FMF is the first step for preventing amyloidosis. Patients' beliefs about medicines and treatment may affect treatment adherence and treatment success. Objectives: The aim of this study was to determine adherence to colchicine treatment and related factors in FMF patients. In addition, patients' beliefs about colchicine, which are one of the important factors affecting the treatment adherence of patients, were evaluated. Methods: Total of 179 patients with FMF was included in this study. The demographic and clinical features and MEFV gene mutations were recorded. The treatment adherence of the patients was assessed using by Compliance Questionnaire on Rheumatology (CQR). The Beliefs About Medicines Questionnaire (BMQ-T) was used to assess patient's beliefs about colchicine. The relationship between compliance of treatment and clinical characteristics of patients were assessed. Results: One hundred thirteen (63.1%) of the patients were male. The mean age of patients was 34.5 ± 12.7 years and mean delay in diagnosis was 6.7 ± 8.4 years. The mean dose of colchicine was 1.37 ± 0.43 mg/day and, the percentage of patients using colchicine regularly was 66.5%. Adherence to treatment was higher in patients with concomitant diseases than those without comorbidities (p = 0.028). In addition, treatment compliance was higher in married patients compared to single patients (p = 0.013). The colchicine dose used in compatible patients was higher than in non-compatible patients (p = 0.033) (Table 1 ). We also found that as the BMQ-T Specific Necessity scores increased, compliance with treatment increased. On the other hand, as the BMQ-T General Overuse and General Harm scores increased, non-compliance with treatment increased (Table 2 ). Conclusion: In patients with FMF, it is important to evaluate the compliance with the treatment due to the importance of colchicine to prevent amyloidosis that may occur in patients without treatment. As this study shows it is also important to determine patients' beliefs about medicine in terms of their influence on patients' compliance with treatment. Disclosure of Interests: None declared